Heterochromatin Protein 1a (HP1a) Partner Specificity Is Determined by Critical Amino Acids in the Chromo Shadow Domain and C-terminal Extension - Mendez, Deanna L. (American Society for Biochemistry and Molecular Biology, 2013)
Drosophila melanogaster Heterochromatin Protein 1a (HP1a) is an essential protein critical for heterochromatin assembly and regulation. Its chromo shadow domain (CSD) homodimerizes, a requirement for binding protein partners that contain a PXVXL motif. How does HP1a select among its many different PXVXL-containing partners? HP1a binds tightly to Heterochromatin Protein 2 (HP2), but weakly to PIWI. We investigated differences in homodimerization and the impact of the C-terminal extension (CTE) by contrasting HP1a to its paralogue, HP1b. HP1a and HP1b differ in the dimerization interface, with HP1a having an Arg at position 188 rather than Glu. We find that while this substitution reduces the dimerization constant, it does not impact the binding surface as demonstrated by unchanged partner binding affinities. However, the CTE (only 4 residues in HP1a as compared with 87 residues in HP1b) is critical; the charged residues in HP1a are necessary for tight peptide binding. Examining a panel of amino acid substitutions in the HP1a CSD, we find that Leu-165 in HP1a interacts with HP2 but not PIWI, supporting the conclusion that different sites in the binding surface provide discrimination for partner selection. Partner sequence is also critical for affinity, as the remaining difference in binding between HP2 and PIWI polypeptides is eliminated by swapping the PXVXL motifs between the two. Taken together, these studies indicate that the binding surface of the HP1a CSD plus its short CTE provide the needed discrimination among HP1a's partners, and that the CTE is important for differentiating the interactions of the Drosophila HP1 paralogs.